Lactate and risk of incident diabetes in a case-cohort of the atherosclerosis risk in communities (ARIC) study. - Stephen P Juraschek; Ghanshyam Palamaner Subash Shantha; Audrey Y Chu; Edgar R Miller; Eliseo Guallar; Ron C Hoogeveen; Christie M Ballantyne; Frederick L Brancati; Maria Inês Schmidt; James S Pankow; J Hunter Young (PLoS ONE)
Background Oxidative capacity is decreased in type 2 diabetes. Whether decreased oxidative capacity is a cause or consequence of diabetes is unknown. Our purpose is to evaluate whether lactate, a marker of oxidative capacity, is associated with incident diabetes. Methods and findings We conducted a case-cohort study in the Atherosclerosis Risk in Communities (ARIC) study at year 9 of follow-up. We evaluated lactate's association with diabetes risk factors at baseline and estimated the hazard ratio for incident diabetes by quartiles of plasma lactate in 544 incident diabetic cases and 533 non-cases. Plasma lactate showed a graded positive relationship with fasting glucose and insulin (P<0.001). The relative hazard for incident diabetes increased across lactate quartiles (P-trend ≤0.001). Following adjustment for demographic factors, medical history, physical activity, adiposity, and serum lipids, the hazard ratio in the highest quartile was 2.05 times the hazard in the lowest quartile (95% CI: 1.28, 3.28). After including fasting glucose and insulin the association became non-significant. Conclusions Lactate, an indicator of oxidative capacity, predicts incident diabetes independent of many other risk factors and is strongly related to markers of insulin resistance. Future studies should evaluate the temporal relationship between elevated lactate and impaired fasting glucose and insulin resistance.